Marginalii la relația Biserică – Stat: Considerații privind clerul și politica în perioada post-comunistă - Kerekes, Nicolae-Dragoș (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
In the present study we propose a radiography of the decisions of the Holy Synod of the Romanian Orthodox Church in the first three post-communist decades (from 1990 to 2020) regarding the involvement of the clergy in politics, one of the many levels of the Church-State relationship.The analysis of the text reveals the fact that, as clearly expressed in the holy canons, as difficult to apply nowadays, the principle of neutrality of the Church in party politics is the red thread of the post-Decemberist attitude with the inveterate oscillations from the canonical rigor to the missionar-pastoral descent.